Interaction of melamine and di-(2-ethylhexyl) phthalate exposure on markers of early renal damage in children: The 2011 Taiwan food scandal. (April 2018) - Wu, Chia-Fang; Hsiung, Chao A.; Tsai, Hui-Ju; Tsai, Yi-Chun; Hsieh, Hui-Min; Chen, Bai-Hsiun; Wu, Ming-Tsang
Abstract: Melamine and phthalate, mainly di-(2-ethylhexyl) phthalate (DEHP), are ubiquitously present in the general environment. We investigated whether urine melamine levels can modify the relationship between DEHP exposure and markers of early renal damage in children. A nationwide health survey for Children aged ≤12 years possibly exposed to phthalates were enrolled between August 2012 and January 2013. They were administered questionnaires to collect details regarding past DEHP exposure to phthalate-tainted foodstuffs. Urine samples were measured melamine levels, phthalate metabolites and biomarkers of renal damage, including urine microalbumin/creatinine ratio (ACR), N-acetyl-beta-d -glucosaminidase (NAG), and β2-microglobulin. The study included 224 children who had a median urine melamine level (μg/mmol creatinine) of 1.61 ranging 0.18–47.42. Positive correlations were found between urine melamine levels and urine ACR as well as urine NAG levels (both Spearman correlation coefficients r = 0.24, n = 224, p < .001). The higher the past DEHP exposure or urine melamine levels, the higher the prevalence of microalbuminuria. An interaction effect was also found between urine melamine levels and past DEHP exposure on urine ACR. Melamine levels may further modify the effect of past DEHP exposure on urine ACR in children. Graphical abstract: Image 1 Highlights: Children aged ≤12 years possibly exposed to phthalates were enrolled. A significant and positive association between urine NAG binary and urine melamine level quartile was found. The higher the past DEHP exposure or urine melamine levels, the higher the prevalence of microalbuminuria. Interactive effect of urine melamine and past DEHP exposure on microalbuminuria was present. Abstract : The higher the past DEHP exposure or urine melamine levels, the higher the prevalence of microalbuminuria. An interaction effect was also found between urine melamine levels and past DEHP exposure on urine ACR. Melamine levels may further modify the effect of past DEHP exposure on urine ACR in children.